Perbandingan Kurikulum Matematika Indonesia dan Kanada: Studi Literatur Kurikulum di Quebec - Sari, Nurul Husnah Mustika; Mulyono, Mulyono; Waluya, St. Budi (Papanda, 2026)
Canada is a country that achieves high PISA scores, both in mathematics and other literacy. This article aims to analyze mathematics in Canada, specifically in the province of Quebec which has the highest PISA mathematics score. The research method used is a literature study with sources of academic documents, research reports, and national and international journal articles. Based on the analysis, it is known that there are several differences in the mathematics curriculum in Quebec (Canada and Indonesia), namely in the objectives of mathematics learning where in Quebec mathematics focuses on solving problems, using mathematical reasoning, and communicating using the language of mathematics. Then, in Quebec financial literacy is part of mathematics and teaching in secondary schools. Meanwhile in Indonesia, financial literacy has not been a focus. Regarding teacher licensing in Indonesia, teachers must master four competencies while in Quebec, there are 13 teacher competency standards. The mathematics problems used in Quebec tend to be open-ended problems that have more than one answer. Meanwhile in Indonesia, the problems used are still predominantly problems that have one correct answer. Another crucial thing is that in Quebec uses socio-constructivism while in Indonesia, academic documents use constructivism and humanism, but in its application is not yet optimal and many still use behaviorism.